Physical Activity and Workplace Stress: Influences on Health Perception Among Academics in Central and Eastern Europe - Kovács, Klára; Michelini, Enrico (Central European Journal of Educational Research, 2024)
Several studies have drawn attention to the unhealthy lifestyles of academic staff (lack of physical activity, unhealthy diet, high levels of stress, etc.). However, few studies have addressed the physical activity (PA) of academics, the problem of inactivity as compared to the average population or university students. Our study aims to determine the role of PA and participation in university sports, as well as other health behaviours and sources and resources of stress at work, on the self-assessed health (SAH) status of academics in five Central and Eastern European countries (Hungary, Ukraine, Slovakia, Serbia and Romania). To answer our research question, we used the database of our international survey (CEETHE 2023, N=821). According to our results, SAH is mainly and positively influenced by PA and health-conscious eating, as well as work engagement, and negatively correlated with age, burnout, work-life conflicts and workplace bullying as work stressors. Based on our findings, workplace interventions including sports and time management programmes are recommended for universities, and a safe working environment is essential to improve academics’ subjective health status.